Impact of distractors in item analysis of multiple choice questions - Burud, Ismail; Nagandla, Kavitha; Agarwal, Puneet (International Journal of Research in Medical Sciences, 2019)
Background: Item analysis is a quality assurance of examining the performance of the individual test items that measures the validity and reliability of exams. This study was performed to evaluate the quality of the test items with respect to their performance on difficulty index (DFI), Discriminatory index (DI) and assessment of functional and non-functional distractors (FD and NFD). Methods: This study was performed on the summative examination undertaken by 113 students. The analyses include 120 one best answers (OBAs) and 360 distractors. Results: Out of the 360 distractors, 85 distractors were chosen by less than 5% with the distractor efficiency of 23.6%. About 47 (13%) items had no NFDs while 51 (14%), 30 (8.3%), and 4 (1.1%) items contained 1, 2, and 3 NFDs respectively. Majority of the items showed excellent difficulty index (50.4%, n=42) and fair discrimination (37%, n=33). The questions with excellent difficulty index and discriminatory index showed statistical significance with 1NFD and 2 NFD (p=0.03). Conclusions: The post evaluation of item performance in any exam in one of the quality assurance method of identifying the best performing item for quality question bank. The distractor efficiency gives information on the overall quality of item.